2012
DOI: 10.24857/rgsa.v6i2.531
|View full text |Cite
|
Sign up to set email alerts
|

NÍVEL DO DISCLOSURE AMBIENTAL DAS EMPRESAS BRASILEIRAS LISTADAS NA BM&FBOVESPA: UMA ANÁLISE DO PERÍODO DE 2006 A 2010

Abstract: Objetivou-se verificar o nível de disclosure ambiental das empresas brasileiras listadas na BM&FBovespa no período de 2006 a 2010. Este estudo justifica-se pela teoria do disclosure voluntário na qual afirma que os gestores podem optar entre o tipo de informação evidenciada aos stakeholders. Para atender ao escopo desse estudo utilizou-se como metodologia a análise de conteúdo realizada nos relatórios da administração, nas notas explicativas e nos relatórios de informações ambientais. A pesquisa foi reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…The disclosure of positive information, recognized in this research, is in line with the theory of voluntary disclosure, which favours the company in a biased way, with the clear purpose of showing it in a good light. This corroborates the findings of Dye (2001), Verrecchia (2001), Fernandes (2012), where the positive information is strategically disclosed and highlighted, while the negative is less so, or omitted, resulting in an absence of information, or the minimization of the disclosure of environmental liabilities. In addition, from the perspective of socio-environmental strategy, it was found that the low disclosure of negative information was specifically made merely to comply with government regulations, as proposed by Alperstedt et al (2013).…”
Section: Description and Analysis Of The Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The disclosure of positive information, recognized in this research, is in line with the theory of voluntary disclosure, which favours the company in a biased way, with the clear purpose of showing it in a good light. This corroborates the findings of Dye (2001), Verrecchia (2001), Fernandes (2012), where the positive information is strategically disclosed and highlighted, while the negative is less so, or omitted, resulting in an absence of information, or the minimization of the disclosure of environmental liabilities. In addition, from the perspective of socio-environmental strategy, it was found that the low disclosure of negative information was specifically made merely to comply with government regulations, as proposed by Alperstedt et al (2013).…”
Section: Description and Analysis Of The Resultssupporting
confidence: 88%
“…Verrecchia, 2001;Dye, 2001;Diamond and Verrechia, 1991) and the Brazilian literature (e.g. Gubiani et al 2012;Coelho et al 2013), but not promoting transparency, as a clear tendency has been found of highlighting the positive aspects, and omitting or minimizing the negative ones, according to the taxonomy proposed by Fernandes (2012).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além disso também são utilizados no processo de comunicação com os stakeholders outros relatórios anuais voluntários os quais recebem nomes variados como relatórios para sustentabilidade, relatório do desenvolvimento sustentável, balanço ambiental, entre outros (Fernandes, 2012;Garcia, Cintra, de Souza Ribeiro, & Dibbern, 2015). Trabalhos como os de Farias (2008), Murcia, Rover, Lima, Fávero e Lima (2008), Rover, Tomazzia, Murcia e Borba (2012), Fernandes (2012), Antal e Van Den Bergh (2013), Burgwal e Vieira (2014), Silva, Lima, Freitas e Lagioia (2015), Braam, Weerd, Hauck e Huijbregts (2016) e Gallego-Álvarez, Lozano e Rodríguez-Rosa (2018), têm identificado maior volume de evidenciação, frequentemente medida essencialmente em função da quantidade de termos relacionados ao tema nos relatórios anuais obrigatórios e voluntários. Sendo assim, o objetivo geral deste trabalho foi propor um modelo para mensuração do nível de evidenciação das ações de enfrentamento as mudanças climáticas a partir de fatores determinantes identificados na literatura.…”
Section: Introductionunclassified